Labor market integration of low-educated refugees: RCT evidence from an ambitious integration program in Sweden - Matz Dahlberg; Johan Egebark; Ulrika Vikman; Gülay Özcan (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
This paper evaluates an ambitious and newly designed program for increased integration in Sweden. The purpose of the program is to help newly arrived, low-educated refugees into employment. The program includes four main components: (1) intensive initial language training, (2)work practice under close supervision, (3) job search assistance, and (4) extended cooperation between the local public sector and firms. An important feature of the program is that the demand side of the labor market, represented by the largest real estate company in Gothenburg, is involved in designing the program. Our evaluation is based on a randomized controlled trial, where potential participants in one of the first waves were randomly assigned to treatment and control groups. The paper presents results from the first two years after randomization. Using inference based on Fisher's exact test, we show that the program has positive effects on employment: around 30 % of the individuals in the treatment group are employed each month during the first year following the end of the program, compared to an average of approximately 15 % in the control group.
Keywords: C93; J08; J15; J23; J61; 330; Refugee immigration; Integration; Randomized experiment; Labor market program